2020
DOI: 10.1186/s10020-020-00217-8
|View full text |Cite|
|
Sign up to set email alerts
|

miRNA-23b as a biomarker of culture-positive neonatal sepsis

Abstract: Background Neonatal sepsis remains an important cause of morbidity and mortality. The ability to quickly and accurately diagnose neonatal sepsis based on clinical assessments and laboratory blood tests remains difficult, where haemoculture is the gold standard for detecting bacterial sepsis in blood culture. It is also very difficult to study because neonatal samples are lacking. Methods Forty-eight newborns suspected of sepsis admitted to the Neonatology Department of the Mother-Child Specialized Hospital o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…We found an under-expression of miR-23b coinciding to Fatmi et al [38], who reported increased levels of miR-23b in EOS, but decreased levels in LOS. Unlike Wang et al [19], who reported miR-15a over-expression in term neonates with LOS, we found an underexpression.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We found an under-expression of miR-23b coinciding to Fatmi et al [38], who reported increased levels of miR-23b in EOS, but decreased levels in LOS. Unlike Wang et al [19], who reported miR-15a over-expression in term neonates with LOS, we found an underexpression.…”
Section: Discussionsupporting
confidence: 86%
“…miR-23 is an important regulator of the innate immune response and several inflammatory processes by targeting metalloproteinase 10 and mediating in the development of myocardial dysfunction [37]. Both have been previously described in full-term neonates with sepsis as potential clinical biomarkers that reflect the disease; nevertheless, they have not been evaluated in VLBW infants [19,38].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a previous study reported differentially expressed plasma soluble CD14 subtypes between EOS and LOS, and emphasized the importance to notice differences when treating EOS and LOS ( 36 ). Furthermore, miR-23b expression, which may serve as a good marker, was upregulated in EOS but downregulated in LOS, and its expression was altered during different neonatal periods ( 37 ). In the present study, only 6 cases of EOS were included in the NS group, which was not sufficient to distinguish EOS from LOS for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated studies have demonstrated that aberrantly expressed miRNAs in human diseases have important clinical significance in diagnosis ( 2224 ). For example, circulating aberrantly expressed miR-132, miR-146a, miR-155, and miR-223 in septic neonates were documented to be related with immune-related genes, and might be candidate biomarkers for neonatal sepsis diagnosis ( 25 ).…”
Section: Discussionmentioning
confidence: 99%